ISOLATION, CHARACTERIZATION AND MONITORING OF ANTIBIOTIC RESISTANCE IN PASTEURELLA MULTOCIDA ISOLATES FROM BUFFALO (BUBALUS BUBALIS) H ERDS AROUND LAHORE - S. Naz; A. Hanif; A. Maqbool; S. Ahmed; K. Muhammand (Journal of Animal and Plant Sciences, 2012)
Haemorragic septicaemia (HS) caused by Pasteurella multocida (P. multucida) is an important disease of buffaloes causing heavy economic losses in Pakistan. Samples from 20 HS suspected carcasses of buffaloes were processed and the recovered isolates were identified by cultural, morphological, biochemical and serological tests. All the isolates were also processed for mouse pathogenicity test and antibiogram assay. Sixteen isolates were identified as Pasteurella multocida. Serologically all isolates were associated with Carter΄s sero group B. Maximum number of isolates were recovered from samples of bone marrow, lungs and spleen. All the isolates were found pathogenic to mice. Antibiogramassay of all the fields isolates depicted the highest sensitivity 87.5% for ciprofloxacin, ofloxacin, enrofloxacin and gentamicin, 81.25% for norfloxacin and amikacin, 75% for kanamycin, 56.25% for tetracycline, 25% for chloramphenicol, doxycycline and vancomycin, erythromycin where as sulfadiazine (12.5%) was found least effective. No resistance was observed for ciprofloxacin, enrofloxacin, ofloxacin and norfloxacin where as maximum resistance was observed against erythromycin and sulfadiazine (50%). It is concluded that all P. multucida isolates belonged to Carter’s group B and found sensitive to ciprofloxacin and ofloxacin.
Keywords: Buffalo; Pasteurella multocida; Isolation; Antibiotic resistance